Introduction to solid state physics - Kittel, Charles (John Wiley & Sons, 2005)
Crystal structure -- Wave diffraction and the reciprocal lattice -- Crystal binding and elastic constants -- Phonons I. Crystal vibrations -- Phonons 11. Thermal properties -- Free electron fermi gas -- Energy bands -- Semiconductor crystals -- Fermi surfaces and metals -- Superconductivity -- Diamagnetism and paramagnetism -- Ferromagnetism and antiferromagnetism -- Magnetic resonance -- Plasmons, polaritons, and polarons -- Optical processes and excitons -- Dielectrics and ferroelectrics -- Surface and interface physics -- Nanostructures -- Noncrystalline solids -- Point defects -- Dislocations -- Alloys.